Implementation of the Afl Guided Inquiry Model to Optimize Learning Outcomes in Acid-Base Titration Material - Maisya Maulida Zahra Nur Firdaus; Muchlis (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
Education in the era of globalization becomes a bridge that connects humans with the global environment in increasing the quality of human resources. This research describes the implementation, students' activities and responses, and the increase in learning outcomes before and after implementing an assessment for learning that is guided inquiry-oriented for Class XI Acid-Base Titration material. A quasi-experimental design with a nonequivalent control group design was used, while data collection instruments were questionnaires and tests. The scores of the guided inquiry model also obtained a score rating of 3-4, or very good, during the meetings. A comparison done through the right-hand t-test for the posttest 1 and posttest 2 analysis yielded a 0.000 p-value reflecting a significant enhancement statistically in the learning outcomes of students, at p < 0.05. Activities by the students were well conducted; the reception of the model was good, as shown by the average percentages, which ranged from 91.42% to 100%, falling within the "very good" range of acceptability.